Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1159/000047311
|View full text |Cite
|
Sign up to set email alerts
|

Which Lead for Q-T Interval Measurements?

Abstract: There are several Q-T interval measures (individual lead, mean Q-T interval or Q-T dispersion) from a 12-lead ECG. Which should be used? As the ECG provides twelve different measures of the heart’s ‘true’ Q-T interval, and as, ‘a priori’, no one measure is any better or worse than any other measure at estimating the ‘true’ Q-T interval, the best measure is the average of these twelve measures, i.e., the mean Q-T interval. The best single lead to measure the Q-T interval is the lead that relates most closely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…Standard methods to measure the T wave offset in biphasic T waves were used. 6,8,9 To reduce error in measurement, the averaged beat was printed at 50 mm/s sweep speed and at 1 mm/mV. Each reader marked Q wave onset and T wave offset (similar to the A-SHM algorithm) for every recording in both LI and LII, and the QT/QTc intervals were then calculated.…”
Section: A-shm Qt Methodsmentioning
confidence: 99%
“…Standard methods to measure the T wave offset in biphasic T waves were used. 6,8,9 To reduce error in measurement, the averaged beat was printed at 50 mm/s sweep speed and at 1 mm/mV. Each reader marked Q wave onset and T wave offset (similar to the A-SHM algorithm) for every recording in both LI and LII, and the QT/QTc intervals were then calculated.…”
Section: A-shm Qt Methodsmentioning
confidence: 99%
“…Davey analyzed his QT dispersion data differently; the QT interval in lead II was correlated with QT interval in each of other 11 leads, the highest correlation coefficient (r ¼ 0.81) was obtained with lead aVF. 22 In another study, Sadanaga et al studied QT dispersion in healthy Japanese subjects and compared it with that in patients receiving psychotropic drugs. As in our study, they too found that the mean QT interval measurement closest to that in lead II (353 AE 29 ms) was observed in lead aVF (351 AE 30 ms) while lead aVL had a mean QT interval measurement farthest from lead II (332 AE 31 ms).…”
Section: Discussionmentioning
confidence: 99%
“…Consideration should be given to the use of invasive arterial pressure monitoring and central venous access (for overdrive pacing of bradycardia/TdP). The QT interval should be monitored in lead V 3 or II, as the QT interval in these leads best approximates the average QT interval (26).…”
Section: Discussionmentioning
confidence: 99%